2005
DOI: 10.1068/c0522
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of the Business Support Infrastructure in Albania: The Need for a Rethink?

Abstract: Introduction: the role of entrepreneurship in economic development It is widely recognised in the literature (Acs and Audretsch, 2003; Audretsch and Keilbach, 2004; Baumol, 2002) that entrepreneurial activity is among the most important determinants of the different economic performances of countries. Entrepreneurship activities and especially small-business activities have been connected to job creation (Audretsch et al, 2001; Bridge et al, 2003; Storey, 1994), economic competitiveness (CEC, 2004; Schumpeter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
4
4
0
Order By: Relevance
“…Therefore, what they receive is not a solution for the problems the faced, but instead will bring new problems for them. This finding is in line with the argument from Xheneti (2005); Smallbone & Welter (2001); and Berry, Sweeting, & Goto (2006).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, what they receive is not a solution for the problems the faced, but instead will bring new problems for them. This finding is in line with the argument from Xheneti (2005); Smallbone & Welter (2001); and Berry, Sweeting, & Goto (2006).…”
Section: Resultssupporting
confidence: 91%
“…This implies that, SME's in Central Java do not have managerial skills in terms of marketing, so understanding and knowledge of the market is crucial to solve. These results are in line with Xheneti (2005); Dominguez & Mayrhofer (2017);and Synovics, Kurt, & Synovics (2018). This has met the Central Java Medium-Term Development Plan (RPJMD) 2013-2018 objective, which aims SME's in the service sector to reach 0.12% of total SME's.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Several studies have also identified access to finance as a barrier to business growth (Hashi, 2001;Bartlett and Bukvič, 2003;Brown et al, 2005). Finally, the legacy of the past, the persistence of customary behaviour and habits, has hindered the effectiveness of the formal institutions established to support SMEs in Albania (Xheneti, 2005). Burdensome regulation and little effective enforcement have also created "perverse" opportunities through increased incentives for corruption (Shleifer and Vishney, 1998;Hellman et al, 2003).…”
Section: Business Growth Theoriesmentioning
confidence: 99%